Effectiveness of interprofessional simulation scenario on knowledge, attitude and practice of hospital-acquired infection control among health professionals in the Klang Valley, Malaysia - Thangarjoo, T. Saraswathy (2022)
Interprofessional learning (IPL) is a key challenge in Malaysia in incorporating the approach into the current profession-specific heathcare training and service. Safe practices would be enhanced with improved collaboration among the health professionals (HPs) when they learn with, from, and about each other. This study evaluated the effectiveness of an innovative approach using interprofessional simulation scenarios (IPSS) in improving knowledge, attitude, and practice (KAP) of hospitalacquired infection control (HAIC) among HPs.The quasi-experimental pre-post test study was conducted in a teaching hospital in Malaysia. Purposive sampling was used to recruit participants from surgical, intensive care, and other units due to constraints in getting participants to attend intervention. Thirty-six health professionals in the experimental and forty in the control group completed the study. All subjects participated in an interactive lecture and demonstrated four IPSS on HAIC (i) taking blood specimen (ii) bedsore dressing (iii) collecting sputum for acid-fast bacilli and (iv) intermittent bladder catheterization. Each team consisted of a doctor and a nurse. A self-administered questionnaire consists of three sections namely i) demography details ii) University of West England Interprofessional (UWEIP) questionnaire with four interprofessional aspects (IP) namely, self-assessment on communication and teamwork skills (CTW), attitude on IPL and interprofessional relationship (IPR) and, perception towards interprofessional interaction (IPI) iii) KAP on HAIC was completed by participants in the pre, immediately and post-intervention timelines. The mean score differences between pre-and post-intervention within groups were tested by employing parametric and non-parametric tests eg., paired sample t-test and, between experimental vs control groups with independence t-test for normally distributed variables. The non-normally distributed data was tested with Wilcoxan signed-rank and Mann- Whitney test respectively. Repeated ANOVA measures were conducted to determine the effectiveness of intervention in the experimental group on the three timelines of data collection. The experimental group showed higher positive scores in post-intervention vs control in the four IPL aspects dimensions and also improved in the KAP scores in HAIC. In CTW, there was no significant difference revealed between post-intervention of the experimental group and post-control group with p > 0.05. In IPL dimension, there was a significant difference between the post-intervention and control groups with, p < 0.05. Similarly, in attitude dimension in HAIC, there was also no significant difference between the post-intervention in experimental and post-control groups with p > 0.05.In IPL aspects there was a significant effect for timeline in pairwise comparison with, Wilks’ Lambda=0.776, F(1, 35) = 4.911, p < 0.05) with η2= 0.224. Likewise in HAIC aspects overall there was a significant effect for timeline, Wilks’ Lambda= 21.910, F(1, 35) = 21.910 , p < 0.05) with η2= 0.563. Infusion of a structured IPL approach and a well-designed IPSSHAIC can be effective in improving KAP in HAIC among health professionals